Administration of 2-deoxy-D-glucose induces pyroptosis in murine breast cancer cells via cAMP/PKA/HK2 to impair tumor survival - Pan, Tingting; Jin, Shengqi; Gao, Wei; Eom, Kidong; Dong, Jing; Li, Lin (Frontiers in Immunology, 2025)
BackgroundBreast cancer poses a severe threat owing to its high morbidity and mortality rates, which are largely attributed to drug resistance. Therefore, novel therapeutic targets need to be identified. Pyroptosis is an inflammatory cell death process mediated by gasdermin (GSDM) and dependent on caspases. Moreover, pyroptosis plays a role in regulating tumor progression and response to therapy. Furthermore, 2-deoxy-D-glucose (2-DG) is a glucose analogue that confers anticancer effects via metabolic interference. However, its mechanism of action in breast cancer remains unclear.MethodsTo explore the effect of 2-DG on pyroptosis in EMT6/4T1 breast cancer cells, cell viability assays, immunoblotting, immunofluorescence, co-immunoprecipitation, and morphological analyses were performed. For in vivo studies, antitumor effects of 2-DG were assessed using xenograft models, and its safety was evaluated by monitoring body weight and conducting histological analysis.Results2-DG induced cytotoxicity and pyroptosis in EMT6/4T1 breast cancer cells. Mechanistically, 2-DG activated cyclic adenosine monophosphate (cAMP)/protein kinase A (PKA) signalling, suppressed hexokinase 2 (HK2), and triggered caspase-3/GSDME-dependent pyroptosis. In vivo experiments demonstrated that 2-DG inhibited breast tumor growth without causing severe toxicity.ConclusionsThese findings identified a novel metabolic-inflammatory axis (cAMP/PKA-HK2-caspase-3/GSDME) in breast cancer. Furthermore, study highlights the in vivo efficacy and safety of 2-DG and its ability to induce pyroptosis, thereby providing a basis for targeting drug resistance in breast cancer.